2008
DOI: 10.1080/09658210801946501
|View full text |Cite
|
Sign up to set email alerts
|

Why do I always have the best ideas? The role of idea quality in unconscious plagiarism

Abstract: Groups of individuals often work together to generate solutions to a problem. Subsequently, one member of the group can plagiarise another either by recalling that person's idea as their own (recall-own plagiarism), or by generating a novel solution that duplicates a previous idea (generate-new plagiarism). The current study examines the extent to which these forms of plagiarism are influenced by the quality of the ideas. Groups of participants initially generated ideas, prior to an elaboration phase in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
15
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
4
15
1
1
Order By: Relevance
“…More pertinently for the current study, it is also hard to reconcile with the pattern repeatedly reported by Stark and Perfect (Perfect & Stark, 2008b;Stark & Perfect, 2006, 2008Stark et al, 2005), in which explicit instruction to elaborate on ideas, either through imagery or improvement, fails to impact on plagiarism rates on generate-new tasks. Perfect and Stark's (2008b) study involved two manipulations during the retention interval. One was that ideas were subject to zero, one, or three improvements.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…More pertinently for the current study, it is also hard to reconcile with the pattern repeatedly reported by Stark and Perfect (Perfect & Stark, 2008b;Stark & Perfect, 2006, 2008Stark et al, 2005), in which explicit instruction to elaborate on ideas, either through imagery or improvement, fails to impact on plagiarism rates on generate-new tasks. Perfect and Stark's (2008b) study involved two manipulations during the retention interval. One was that ideas were subject to zero, one, or three improvements.…”
mentioning
confidence: 57%
“…One day later, the participant returned to recall his or her own ideas and to generate new ideas. On the basis of the work of Perfect and Stark (2008b), we expected participants to plagiarize ideas that were improved in the recall task and to plagiarize the ideas from experts in the generate-new task.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A phenomenon similar to error bias has also been observed in adult-adult peer relationships (e.g., Foley, Fried, Cowan, & Bays, 2014;Perfect, Field, & Jones, 2009;Perfect & Stark, 2008). In one study, pairs of university students memorized plural words in turn, and one of the pair observed the partner's activity.…”
Section: Highlightsmentioning
confidence: 66%
“…)や,人名 や国名などの固有名詞 (Brédart, Lampinen, & Defeldre, 2003) を挙げる課題,マトリックス形式で示されたい くつかの文字から意味のある単語を作成する Boggle と 呼 ば れ る 課 題 (Marsh & Bower, 1993;Marsh & Landau, 1995 (Marsh, Landau, & Hicks, 1997;Perfect, Field, & Jones, 2009) ,日 常的な物品の新たな使い方を考える課題 (Perfect & Stark, 2008b;Stark, Perfect & Newstead, 2005;Stark & Perfect, 2006) ,新たな生物や玩具,道具などを考案す る描画課題 (Dow, 2015;Marsh, Landau, & Hicks, 1996;Smith, Ward, & Schumacher, 1993)などが用いられた。 「他者」の性質 cryptomnesia の際の情報源となりう る「他者」の種類についても多少のバリエーションが みられる。最初の生成課題が複数の実験参加者で行わ れ「他者」が文字どおり他の人間である場合 (Brown & Murphy, 1989;Perfect et al, 2009)と, 「他者」が人間 ではなくたとえばコンピューターであり,実験参加者 と交代で生成課題を行う場合 (Marsh & Bower, 1993;Marsh & Landau, 1995) (Landau et al, 2000;Marsh et al, 1996) Marsh & Bower(1993) および Marsh & Landau(1995) は,いずれの cryptomnesia も記憶痕跡の強度判断を誤 るために生じるという仮説を立て,次のようなモデル を提案した( Figure 1) 。彼らの実験では,Boggle と呼 ばれる単語生成課題が用いられた。このモデルでは, 生成課題終了後の実験参加者の記憶内に,痕跡強度の 分布が異なる 3 種類の記憶痕跡が生じると仮定する。 この 3 種類は,痕跡の強い方から,生成課題で参加者 自らが生成した単語(subject-generated items,Figure 1 では S)の記憶痕跡, 他者(彼らの実験ではコンピュー タ ー) が 生 成 し た 単 語(computer-generated items, (Stark & Perfect, 2008) (Brown & Halliday, 1991;Landau et al, 2000;Marsh & Bower, 1993;Marsh & Landau, 1995) Stark, 2008b;Stark & Perfect, 2006Stark et al, 2005) 。イメージ的精緻化の結果としては,減少 する場合もあるが (Stark et al, 2005) ,多くの実験で は影響を受けなかった (Perfect & Stark, 2008a;Stark & Perfect, 2006 (Marsh et al, 1996) 。 非単語を材料とした実験でも同様のことが示されて いる。たとえば,昆虫や薬などの新たな名称(つまり 非単語)を考案する...…”
unclassified